Pancasila Educational Values in Indicators Religious Moderation in Indonesia - Donny Khoirul Azis; Made Saihu; Akmal Rizki Gunawan Hsb; Athoillah Islamy (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
The phenomenon of radicalism and terrorism in the name of religion in Indonesia is still showing its stretching in various existing cases. Responding to this problem requires the objectification of character education values for the Indonesian people in the context of forming a moderate mindset and attitude in their social and religious life. This research intends to identify the dimensions of Pancasila educational values in the four indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia. This qualitative research is in the form of a literature review with a normative-philosophical approach. The results of the study conclude that there are dimensions of Pancasila educational values contained in the four indicators of religious moderation in Indonesia. First, the educational value of the first precepts in the indicator of tolerance in the form of educational values in shaping the mindset and attitude of respecting and respecting various distinctive aspects of religious pluralism. Second, the educational value of the second precept in the indicator of anti-radicalism attitudes in the form of educational values in forming awareness of attitudes to uphold the values of the benefit of human life. Third, the educational value of the third precept in the indicator of national commitment in the form of awareness of the attitude of upholding the values of unity and unity in the frame of state life in Indonesia. Fourth, the educational value of the fourth and fifth precepts in adaptive indicators to local culture in the form of being democratic and making the value of social justice in responding to diversity related to local wisdom. The theoretical implication of the findings of this study shows that the construction of ideas in the formulation of the four indicators of religious moderation in Indonesia has a normative-universal value base that becomes the ideology of the Indonesian nation, not the ideology of a particular religion or group.